Drug versus non‐drug behaviors: A dual‐reward model of sex differences and neurobiological mechanisms in rats. Issue 3 (17th March 2022) - Nall, Rusty W.; Chalhoub, Reda M.; Kalivas, Peter W.
Abstract : Substance Use Disorders (SUDs) are an impactful problem characterized by chronic relapse and engagement in drug‐related behaviors at the expense of non‐drug behaviors. Brain regions implicated in drug and non‐drug‐related behaviors often overlap, complicating investigations of neurobiological mechanisms underlying SUDs. Here we presented a within‐subject model for studying self‐administration, reinforcer competition, extinction, and cued reinstatement of cocaine‐ and food‐seeking in rats. Due to differences in cocaine‐ and food‐reinforced behavior, we transformed data to proportions of baseline, revealing increased resistance to extinction and disproportionately greater cued reinstatement of cocaine seeking relative to food seeking. Consistent with previous reports, females showed greater preference for cocaine reinforcement than males, though these findings failed to reach statistical significance. To demonstrate the model's utility for investigating neurobiological mechanisms, we included proof‐of‐concept calcium imaging data demonstrating the utility of the behavioral model for detecting cellular activity patterns associated with cocaine‐ and food‐seeking behaviors. Future studies utilizing this model should improve understanding of the development and expression of pathological behaviors characteristic of SUDs in humans, sex differences in these behaviors, and their neurobiological correlates. Thus, the model has utility for improving understanding of SUDs, leading to novel treatments to reduce the pathological behaviors associated with SUDs.